Morphoagronomic characterization of a germplasm collection of Furcraea spp. and Agave spp. - Medina Cano, Clara Inés; Grisales Vásquez, Nancy Yohana; Orozco Orozco, Luz Fanny; Barbosa Ángel, Edwin Samir; Vargas Arcila, María Orfilia; Cotes Torres, José Miguel (Revista Ceres, 2022)
This work was carried out in Antioquia, Colombia, in a collection of the Furcraea and Agave genera, important in the country for manufacturing strings, sacks, geotextiles, and handicrafts Currently, to enhance its use, applications have been developed in textiles, biodegradable materials and thermo-acoustic insulation, among others. The aim of this study was to characterize phenotypically and agronomically 94 accessions. The variables were weighted according to the degree of discrimination; a dissimilarity dendrogram was constructed using UPGMA based on Gower’s distance, and the cophenetic correlation coefficient was determined. Six groups were identified; on the one hand, the accessions of the Agave genus formed groups A and B, with and without spines, respectively, showing the highest elongation values. On the other hand, the Furcraea accessions formed groups C to F, with the highest average values of fiber per plant, allowing a first approach to identify promising clones for their use per se or utilized in plant breeding programs. This study represents an approach to knowing the morphological and agronomic variability of the collection and highlights the importance of maintaining the germplasm bank for ex situ conservation.